1995
DOI: 10.1172/jci118121
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone increases the concentration of insulin-like growth factor-I and transforming growth factor beta 1 in rat bone.

Abstract: Intermittent treatment with parathyroid hormone (PTH) increases bone mass in experimental animals and humans. In vitro studies have suggested that the anabolic effect of PTH may be mediated by local growth factors. However, the relevance of these findings to in vivo situations remains unclear. In this study, we examined a time course of daily s.c. injections of hPTH(1-34) on the skeletal concentration of insulin-like growth factor (IGF)-I, IGF-II, and transforming growth factor (TGF-.3) in the proximal tail ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(96 citation statements)
references
References 37 publications
5
89
0
2
Order By: Relevance
“…They concluded that both growth factors had synergistic effects on fracture healing. Similar conclusions were drawn by other authors [33,43].…”
Section: Fluorochrome Analysis Resultssupporting
confidence: 93%
“…They concluded that both growth factors had synergistic effects on fracture healing. Similar conclusions were drawn by other authors [33,43].…”
Section: Fluorochrome Analysis Resultssupporting
confidence: 93%
“…The images were stored in three-dimensional arrays with an isotropic voxel size of either 34 m (for the whole bone) or 9 m (for the distal femoral metaphysis). Morphometric parameters were computed using a direct three-dimensional approach that does not rely on any assumptions about whether the underlying structure is either plate or rod-like (25). For the whole bone, we computed the total bone volume (BV, mm 3 ) and the apparent volume density (AVD, %), defined as the percent of mineralized tissue volume divided by the total volume defined by the external bone envelope (24).…”
Section: Methodsmentioning
confidence: 99%
“…As in human cells, in vitro PTH stimulation increases of production of TGFb1 and IGF-1 by murine osteoblasts (Cho et al, 2013, McCarthy et al, 1989, Pfeilschifter et al, 1995. However, the effects of iPTH treatment on the production of these factors is largely unknown.…”
Section: Ipth Treatment In Mice Expands the Pool Of Murine Bm Tregs Bmentioning
confidence: 99%
“…Recently, IGF-1 has been recognized as an additional inducer of Tregs (Anguela, Tafuro et al, 2013, Johannesson, Sattler et al, 2014. Since iPTH increases TGFb and IGF-1 production in bone (Cho, Pirih et al, 2013, McCarthy, Centrella et al, 1989, Pfeilschifter, Laukhuf et al, 1995, it is likely that iPTH may induce and/or expand BM Tregs.…”
Section: Introductionmentioning
confidence: 99%